Concept paper pathology education transformation - Imad Ibrahim Ali Al-Sultan; Jasni Sabri (2015)
This paper is concerned with understanding of recent developed thoughts and ideas on teaching and learning pathology. The science of pathology as a disease teaching topic for medical and related science students is one of most important discipline for medical practice in academic teaching. The trend of teaching in these fundamental subjects in the past and current situation is reviewed with the existence of challenges facing the academic teaching and learning process. Reforms and transformation is linked to the style of new framework restructure of teaching process in the medical institutions.